TRANSLATION, TRANSCULTURAL ADAPTATION, VALIDATION OF THE HOLISTIC CRITICAL THINKING SCORING RUBRIC TO BRAZILIAN PORTUGUESE - Riegel, Fernando; Crossetti, Maria da Graça Oliveira (Revista Contexto & Saúde, 2019)
Objective: translation, transcultural adaptation, and validation of the Holistic Critical Thinking Scoring Rubric, original from the United States, to Brazilian Portuguese. Method: methodological study comprising the following steps: translation by 3 independent translators, transcultural adaptation by a Committee of 6 Nurses Experts; and validation, with the participation, in the pre-test, of 30 academics and 3 teachers-evaluators of Nursing field. The validity and reliability of the tool were verified by Kappa test. Results: the Portuguese version of the tool obtained a Kappa test score of 0.82 in the pre-test group. There was strong significant agreement among the evaluators. Conclusion: The Brazilian version of the Holistic Critical Thinking Scoring Rubric is a valid and reliable tool to evaluate the holistic critical thinking of Nursing academics at different levels of training, especially using active teaching methodologies.